Analisis Akad Wakalah Pada Transaksi Financial Technology Syariah - Citra Kirana Astika Putri; Jihan Anggraini; Hana Rahmah Kamila; Faisal Al Fadli; Fadhli Suko (Al-bank: Journal of Islamic Banking and Finance, 2023)
This study aims to analyze the application of the wakalah contract in the sharia fintech digital payment system in one of the sharia fintech service products in Indonesia. This type of research is a literature study with a quantitative descriptive approach. The results showed that the wakalah contract in Islamic financial technology transactions is allowed if the issuer and the parties organizing electronic money and digital financial service agents do not use an ijarah contract. This is in accordance with DSN-MUI Fatwa No. 10/DSN-MUI/IV/2000 concerning wakalah which applies rewards to wakalah contracts. Instead of renting services, the issuer represents its duties to the parties organizing electronic money including digital financial service agents. So that the results of this study can be a guideline in making and formulating policies.